Monogenéticos parasitos de peixes da ordem Characiformes provenientes do rio Batalha, médio rio Tietê, São Paulo, Brasil - Dias, Karina Gabriele Alves [UNESP] (2017)
Global biodiversity has been very discussed and some authors have argued of the species of parasites as a fundamental part of this. Thus the aim of the study was to obtain a better understanding of the monogeneans biodiversity of four fish species: Cyphocharax modestus (Fernández-Yépez, 1948), Moenkhausia intermedia (Eigenmann, 1908), Serrasalmus maculatus (Kner, 1858) and Roeboides descalvadensis (Fowler, 1932) from Batalha River, São Paulo State, Brazil. During the period from November 2014 to December 2014, four collections were carried out and with 120 fish caught (30 of each species). Nine species of dactylogirids were found: Curvianchorathus singularis, Dactylogyridae gen. sp., Calpidothecium sp., Palombitrema triangulum, Jainus hexops, Jainus amazonesis, Rhinoxenus piranhus, Anacanthorus sciponophallus and Notozothecium minor. In relation to the species C. modestus, 33% of the specimens were parasitized by monogenetics, being the species: C. sigularis (Prevalence - P = 23.33%, mean intensity - I = 4.14±0.5 and mean abundance - A = 0.97±0.4), P. triangulum (P = 17%, I = 4±0.4, A = 0.67±0.3), Dactylogyridae gen. sp. (P = 3%, I = 1, A = 0.03±0.5) and Calpidothecium sp. (P = 3%, I = 2, A = 0.07±0.4). S. maculatus presented a total prevalence of parasitism by monogenetic species of 87%. The species were: A. sciponophallus (P = 73.33%, I = 22±4.47, A = 16.13±4.0), R. piranhus (P = 70%, I = 5.81±0.94, A = 4.07±0.9) and N. minor (P = 30%, I = 7±1.58, A = 2.1±1.02). M. intermedia and R. descalvadensis presented total prevalence of parasitism by monogenetics of 56.7% and 66.7%, respectively. The same species of monogenetics were found in these two hosts: J. hexops (P = 56.7% and P = 66.7%, I = 2.1±0.18 and I = 6.15±1.18, A = 1.2±0.24 and A = 4.1±1.1) respectively. In M. intermedia we also found J. amazonensis (P = 6.7%, I = 1, A = 0.07±0.04). The results described can be used as source of information about diseases of and to recognize the habitat aspects and biology of their hosts.